Kesejahteraan Subjektif pada Pemulung : Studi Kasus pada Seorang Pemulung di KP. Tenggilis Mustika Jaya - Nurjono, Syifa Zam Zami; Yazid, Farhan; Nuristiyanto, Bagus; Johan, Chintia Devi; Saefuddin, Muhammad; Rasid, Musyari; Larasati, Yunisa; Abdillah, Rijal (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The subjective well-being of scavengers is often influenced by constrained economic and social circumstances; nonetheless, they may experience contentment in everyday life due to social support and resilience. This research employs a qualitative methodology using a case study technique to investigate the subjective wellbeing of a scavenger with over 25 years of experience at Kp. Tenggilis Mustika Jaya, via comprehensive interviews and direct observation. The study's findings indicate that despite economic hardships and adverse living situations, scavengers may sustain a positive subjective well-being, bolstered by cognitive, emotional, and social dimensions that enhance their life satisfaction. This welfare is reinforced by positive attitudes, flexibility, and social support from the surrounding environment.